"We Can Work It Out": The Place of Work in Italian Psychosocial Rehabilitation. Issue 1 (2nd January 2016) - Fioritti, Angelo; Peloso, Paolo Francesco; Percudani, Mauro
Abstract: In this paper the relation between psychosocial rehabilitation and job in Italy, a theme that can be traced back to two cultural roots, that of the right to work enshrined in the Italian Constitution and that of the ergotherapy in the asylum tradition, is stressed. After 1978 the efforts to assure community psychiatry patients a job opportunity has led to the emergence of cooperatives against exclusion. The story of one of them was told in an Italian movie, in which it is possible to understand the main problems of rehabilitation through labor. In recent decades, the transformation of Italian society and the evolution of services has necessitated the evolution of cooperatives to social enterprise, which respond to a different philosophy, and a broader range of opportunities, with the introduction of new models, such as IPS. The example of two regional projects of the last years is here illustrated.